In vivo expansion of activated naive CD8+ T cells and NK cells driven by complexes of IL-2 and anti-IL-2 monoclonal antibody as novel approach of cancer immunotherapy - Tomala, Jakub; Chmelova, Helena; Mrkvan, Tomas; Rihova, Blanka; Kovar, Marek (Journal of immunology (Baltimore, Md., 2009)
IL-2 is potent imunostimulatory molecule that plays a key role in T and NK cell activation and expansion. IL-2 is approved by the FDA to treat metastatic renal cancer and melanoma, but its extremely short half-life and serious toxicities are significant limitations of its use. It was reported that in vivo biological activity of IL-2 can be increased by association of IL-2 with anti-IL-2 mAb (S4B6). IL-2/S4B6 mAb immunocomplexes were described to be highly stimulatory for NK and memory CD8(+) T cells and intermediately also for regulatory T cells. IL-2/JES6-1 mAb immunocomplexes are stimulatory solely for regulatory T cells. In this study we show that although both mentioned IL-2 immunocomplexes are less potent than free IL-2 in vitro, they possess extremely high stimulatory activity to expand activated naive CD8(+) T cells in vivo. IL-2 immunocomplexes expand activated naive CD8(+) T cells several hundred-fold times after four doses and more than 1000-fold times after six doses (1.5 microg/dose of IL-2), whereas free IL-2 given at the same dosage shows negligible activity. IL-2/S4B6 mAb immunocomplexes also induce massive expansion of NK cells (40% of DX5(+)NK1.1(+) cells in spleen). Importantly, activated naive CD8(+) T cells expanded by IL-2 immunocomplexes form robust population of functional memory cells. We also demonstrate in two distinct tumor models that IL-2/S4B6 mAb immunocomplexes possess considerable antitumor activity. Finally, by using radioactively labeled IL-2, we provide for first time direct evidence that IL-2 immunocomplexes have much longer half-life in circulation than free IL-2, being approximately 3 h vs <15 min, respectively.
Keywords: Interleukin-2; nádorové buněčné linie; Adoptive Transfer; Mice, Inbred BALB C; Killer Cells, Natural; myši transgenní; rekombinantní proteiny; monoklonální protilátky; myši inbrední C57BL; Antigen-Antibody Complex; mužské pohlaví; Antibodies, Monoclonal; Mice; Cell Line, Tumor; Recombinant Proteins; imunokomplex; interleukin-2; poločas; Neoplasms; CD8-pozitivní T-lymfocyty; ženské pohlaví; imunoterapie; zvířata; nádory; myši inbrední BALB C; Half-Life; myši; Immunotherapy; převzatá imunita; buňky NK; CD8-Positive T-Lymphocytes; Female; Mice, Transgenic; Mice, Inbred C57BL; Male; Animals